2019
DOI: 10.1002/lary.27858
|View full text |Cite
|
Sign up to set email alerts
|

Add‐on probiotics in patients with persistent allergic rhinitis: A randomized crossover clinical trial

Abstract: Objectives Current medications for allergic rhinitis (AR) may have undesirable side effects that could affect quality of life (QoL). Probiotics could be an alternative in these patients. The aim of this study was to assess the impact of add‐on probiotics on symptoms and QoL of patients. Methods In this randomized crossover clinical trial, patients with persistent AR were included. Each subject received budesonide with probiotic supplements (BP) or budesonide with placebo for 8 weeks (B), then vice versa for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 38 publications
(56 reference statements)
1
12
2
4
Order By: Relevance
“…thermophilus ) with intranasal budesonide or intranasal budesonide with placebo for 8 weeks. The addition of probiotics significantly improved quality of life in persistent rhinitis patients [ 135 ]. Another research group evaluated the effect of L. rhamnosus GG and vitamin D supplementation on the effectiveness of grass-specific sublingual immunotherapy (SLIT) in children.…”
Section: Results: Evidence Of Efficacy Of Probioticsmentioning
confidence: 99%
“…thermophilus ) with intranasal budesonide or intranasal budesonide with placebo for 8 weeks. The addition of probiotics significantly improved quality of life in persistent rhinitis patients [ 135 ]. Another research group evaluated the effect of L. rhamnosus GG and vitamin D supplementation on the effectiveness of grass-specific sublingual immunotherapy (SLIT) in children.…”
Section: Results: Evidence Of Efficacy Of Probioticsmentioning
confidence: 99%
“…The survey is constructed for self-administration. The SF-36 has also been widely used when measuring effects of allergic rhinitis on everyday life 48…”
Section: Methods and Analysismentioning
confidence: 99%
“…Probiotic-assisted combination therapy is also an important area of focus. In a study using a Gram-positive oral probiotic formulation ( Familact capsules) in combination with budesonide, Jalali et al 58 found that the addition of probiotics significantly improved the quality of life of AR patients compared with budesonide alone (according to SNOT-22 and control test scores for allergic rhinitis and asthma). The benefits of combined treatment with probiotics and AIT have also been studied.…”
Section: Probioticsmentioning
confidence: 99%